Impacts of poor management on construction project in Malaysia - Nurul Ain Syafiqah, Sabri (2018)
Project management is a system that involved development, changes, and innovation in an operation work. Some of the activities involved are planning and controlling project, and these two activities depend on a budget that had been stated, so the project can be completed in a given time. Based on this definition, it is clearly shown that a good and effective management system is needed in any of the construction projects. Construction project involved many parties such as contractor, sub-contractor, engineer, safety officer, architect, consultant and etc. Meanwhile, the project must be completed within its budget and time to deliver the project, while maintaining their quality at its best. Thus, an ineffective management system in construction will give negative impacts on a construction project. As can be seen today, there are many sick and delayed projects in Malaysia, and the main factor that contributes to this problem is poor management of the project itself. Poor management in the construction industry is a global phenomenon and construction industry in Malaysia is no exception too. Thus, this study is conducted to identify the main factors that contribute to the poor and ineffective management system in the construction industry, and how this problem could give impacts on a construction project. In additions, possible solutions to this problem are also recommended in this study. A questionnaire survey was conducted in order to gain data related to poor management from various parties involved in this industry. The analysis shows that the main factors that could contribute to poor management are communication problems while the main impact of poor management is delay of the project.